Prognostic Utility of the Braden Scale and the Morse Fall Scale in Hospitalized Patients With Heart Failure. (April 2017) - Carazo, Matthew; Sadarangani, Tina; Natarajan, Sundar; Katz, Stuart D.; Blaum, Caroline; Dickson, Victoria Vaughan
Geriatric syndromes are common in hospitalized elders with heart failure (HF), but association with clinical outcomes is not well characterized. The purpose of this study ( N = 289) was to assess presence of geriatric syndromes using Joint Commission-mandated measures, the Braden Scale (BS) and Morse Fall Scale (MFS), and to explore prognostic utility in hospitalized HF patients. Data extracted from the electronic medical record included sociodemographics, medications, clinical data, comorbid conditions, and the BS and MFS. The primary outcome of mortality was assessed using Social Security Death Master File. Statistical analysis included Cox proportional hazards models to assess association between BS and MFS scores and all-cause mortality with adjustment for known clinical prognostic factors. Higher risk BS and MFS scores were common in hospitalized HF patients, but were not independent predictors of survival. Further study of the clinical utility of these scores and other measures of geriatric syndromes in HF is warranted.